2023
DOI: 10.1261/rna.079375.122
|View full text |Cite
|
Sign up to set email alerts
|

Principles, mechanisms, and biological implications of translation termination–reinitiation

Abstract: The gene expression pathway from DNA sequence to functional protein is not as straightforward as simple depictions of the Central Dogma might suggest. Each step is highly regulated, with complex and only partially understood molecular mechanisms at play. Translation is one step where the “one gene-one protein” paradigm breaks down, as often a single mature eukaryotic mRNA leads to more than one protein product. One way this occurs is through translation reinitiation, in which a ribosome starts making protein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 182 publications
0
7
0
Order By: Relevance
“…The distance between PTC and the nearby AUG may be a key determinant for the reinitiation efficiency. If the translation reinitiation starts from an in-frame AUG, an N-terminal truncated protein will be produced, which may maintain certain functionality [ 47 , 48 ].…”
Section: Translation Reinitiationmentioning
confidence: 99%
“…The distance between PTC and the nearby AUG may be a key determinant for the reinitiation efficiency. If the translation reinitiation starts from an in-frame AUG, an N-terminal truncated protein will be produced, which may maintain certain functionality [ 47 , 48 ].…”
Section: Translation Reinitiationmentioning
confidence: 99%
“…In contrast, an upstream AUG preceding the main ORF start codon can be in an overlapping ORF, with 2 further subclasses: out-of-frame overlapping uORFs (oORFs), the stop codons of which are downstream of main ORF AUGs and in different reading frames, and N-terminal extensions, which are basically overlapping uORFs in-frame with the main ORF [ 140 , 141 , 142 , 143 , 144 ] ( Figure 1 ). The downstream CDS can be engaged by the re-initiating PIC only when the translated uORFs do not overlap with CDSs [ 145 ], or in special cases through a TURBS (termination upstream ribosome binding site) RNA element at the end of the preceding ORF (reviewed in [ 145 , 146 ], see below) ( Figure 1 ). In addition to leaky scanning, bi-directional scanning of the PIC between closely spaced start codons, as in oORFs, can influence start site selection [ 147 , 148 ].…”
Section: Upstream Open Reading Framesmentioning
confidence: 99%
“…In these cases, the uORF stop codon and downstream ORF start codon are in close proximity, out-of-frame, or overlap in consecutive nucleotides. The viral TURBS regulates reinitiation through base-pairing with 18S rRNA and tethering of the post-termination 40S subunit (reviewed in [ 145 , 146 ]). It has been suggested that uORFs in the 5′UTR regulate translation of cellular SLAMF1 mRNA utilizing a TURBS-like element, highlighting shared strategies in eukaryotic translational control [ 170 ].…”
Section: Upstream Open Reading Framesmentioning
confidence: 99%
“…Reinitiation is a poorly understood process [33][34][35][36] that includes (a) the transition from the post-termination state to the scanning-competent state, (b) the reacquisition of eIF2, and (c) the scanning itself. The reinitiated scanning ribosomes can potentially interfere with ribosomes translating a downstream ORF (POLGARF in our case), as they do in the case of eIF4G2-dependent leaky scanning.…”
Section: A Contribution Of Eif4g2 To Reinitiation and Leaky Scanning ...mentioning
confidence: 99%